2017
DOI: 10.1007/s10113-017-1253-y
|View full text |Cite
|
Sign up to set email alerts
|

A media framing analysis of urban flooding in Nigeria: current narratives and implications for policy

Abstract: A critical element of current flood management is the importance of engaging key policy actors when policy decisions are to be made. However, there is still only limited understanding of how narratives of flood management actors may influence flood management policies, even though there is a suggestion that actors can strategically use their narratives to influence policy directions. In a developing country like Nigeria, there are still questions around lessons that can be learnt from understanding the narrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 75 publications
1
33
0
1
Order By: Relevance
“…However, preparedness activities were less prevalent in discussion than the prevention and response activities. This accords with findings from media discourse [15]. Stakeholders' view was also borne out by the household and business surveys that implied a shortfall of communication of information to households and businesses by governmental and non-governmental sources.…”
Section: Government Stakeholder Perspectivessupporting
confidence: 68%
See 1 more Smart Citation
“…However, preparedness activities were less prevalent in discussion than the prevention and response activities. This accords with findings from media discourse [15]. Stakeholders' view was also borne out by the household and business surveys that implied a shortfall of communication of information to households and businesses by governmental and non-governmental sources.…”
Section: Government Stakeholder Perspectivessupporting
confidence: 68%
“…More specifically, in Nigeria there is currently no database that organises key information on flooding either at a national or sub-national level. There are only records of selected recent floods which are by no means complete [15]. In Nigeria, the lack of information and awareness is noted and general calls for improvement in awareness are made [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is clearly known that control and management may not provide the ultimate panacea for flood hazards, but it will provide a perspective to improve its impacts on human activities, lives and property. Specific to Nigeria, Adekola and Lamond [22] and Olowu and Sako [49] state infrastructure and an absence of appropriate legal controls is crucially needed. As a result, inadequate access to resources It is important to note that a significant and crucial factor in saving lives includes trying to control flood occurrence or, at the minimum, to minimize vulnerability within affected areas.…”
Section: Discussion: Flood Control and Managementmentioning
confidence: 99%
“…Methodologies have not adequately assessed flood hazards, in all of the flood prone areas, however, a lack of application within small urban watersheds, focused on generating rainfall and runoff data in urban areas, often correlate where no major rivers exist. Two reasons for this flood-complexity are development practices used in urban areas and a lack of advanced technological methods for capturing geographical data [21,22]. As a consequent, the risk of overflow from the Niger River, spanning much of West Africa, funnels via southern Nigeria and all its minor tributaries ( Figure 2).…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Literally, these efforts, which are being motivated by the Kogi's flooding experience, promote collaborative flood disaster management. However, Adekola and Lamond [63] found that collaborative flood disaster management in Nigeria, which is essential to build community resilience to floods, must engage the governments, communities, businesses, multilateral, and nongovernmental organizations.…”
Section: Conclusion: Mediating the Challenges And Spotlighting Researmentioning
confidence: 99%